STUDY OF THE PHYSICAL AND MECHANICAL PROPERTIES OF CONCRETE WITH COMPLEX CHEMICAL ADDITIVES - Ergashev Mahmudjon Mamadjanovich (Academia Science Repository, 2023)
Currently, one of the available and effective methods of purposefully forming the structure of cement stone, which is characterized by high productivity and strength characteristics, is the modification of concrete with chemical additives. Various types of complex chemical additives are used in the production technology of strong and durable concrete in Uzbekistan and developed foreign countries. However, the chemical additives used by the producers of the Republic of Uzbekistan in the production technology of concrete and reinforced concrete products are very limited. The article explored the problems of creating strong and durable concrete and its chemical additives with energy-saving technology based on local raw materials.